Zambia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This Selected Issues paper and Statistical Appendix examines the economic developments in Zambia during the 1990s. Economic activity recovered significantly in 1996. Real GDP expanded by almost 6 1\2 percent, compared with a cumulative decline of 12 1\2 percent in 1994-95. Good rains stimulated agricultural production, while the other nontraditional and mining sectors also contributed to the turnaround in economic activity. However, owing to a sharp deterioration in the terms of trade, largely on account of falling copper prices, real national income increased by only 2 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet